2020
DOI: 10.1007/s11606-020-06238-7
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning to Develop and Internally Validate a Predictive Model for Post-operative Delirium in a Prospective, Observational Clinical Cohort Study of Older Surgical Patients

Abstract: ORIGINAL RESEARCHwith a model developed using traditional stepwise logistic regression (AUC = 0.69, 95% CI 0.57-0.82). Calibration for all models and feature sets was poor. CONCLUSIONS: We developed machine learning prediction models for post-operative delirium that performed better than chance and are comparable with traditional stepwise logistic regression. Delirium proved to be a phenotype that was difficult to predict with appreciable accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 45 publications
0
47
2
2
Order By: Relevance
“…With the full data of 71 items, the AUCs in this study were 0.62 up to 0.71. Thus, all prediction models in SAGES were numerically less accurate (Racine et al, 2020) than the shorter models.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…With the full data of 71 items, the AUCs in this study were 0.62 up to 0.71. Thus, all prediction models in SAGES were numerically less accurate (Racine et al, 2020) than the shorter models.…”
Section: Discussionmentioning
confidence: 93%
“…In the Successful Aging after Elective Surgery (SAGES) cohort (Racine et al, 2020), a stepwise logistic regression and machine learning algorithms were used to predict POD in elective surgery of 560 older adults. With a limited data set of 18 items in different machine learning methods, they showed AUCs from 0.53 to 0.57, while in another analysis, adding cognitive performance using the modified Mini-Mental-State 3MS (Teng and Chui, 1987) showed intermediate AUCs (0.53-0.68).…”
Section: Discussionmentioning
confidence: 99%
“…All the models presented in these studies show better performance when compared to a clinical tool. Another recent study have developed a predictive model for post-operative delirium in older surgical patients with better performances than chance, but with similar performances when compared with the traditional stepwise logistic regression [ 26 ]. Another recent study has showed the high predictive ability of RF model in detection delirium based on CAM and delirium observation screening scale (DOSS) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In literature, there are several tools for facilitating delirium detection [ 22 , 23 ], such as the Confusion Assessment Method (CAM) [ 24 ], 4AT test [ 25 ], and the most recent Nursing DElirium SCreening (Nu-DESC) tool [ 19 ]. Both CAM [ 26 , 27 , 28 ] and Nu-DESC scales were used to compare the ability of random forest (RF) models in predicting the risk of delirium episodes. The structure of these tools shows similar domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation